Pengembangan tes kemampuan fisik bolabasket siswa SMA putra di Provinsi Daerah Istimewa Yogyakarta - Setyawan, Taufiq Arif; Sugiyanto, FX (Jurnal Keolahragaan, 2016)
Penelitian ini bertujuan untuk mengembangkan tes kemampuan fisik bolabasket yang valid dan reliabel yang dapat digunakan untuk mengukur tingkat kemampuan fisik pemain bolabasket siswa SMA di Daerah Istimewa Yogyakarta (DIY). Subjek penelitian adalah 156 siswa SMA putra di DIY. Produk yang dikembangkan adalah tes kemampuan fisik bolabasket siswa SMA. Langkah pertama sampai keenam merupakan tahap pengembangan standar indikator keterampilan fisik bermain bolabasket siswa SMA. Langkah ketujuh sampai kesepuluh merupakan tahap pengembangan instrumen. Hasil uji skala kecil digunakan sebagai uji coba pengembangan produk dilakukan untuk keperluan pengujian validitas dan reliabilitas instrumen tes. Uji lanjut pada skala besar difokuskan untuk menyusun norma dan standar penilaian atas instrumen tes keterampilan fisik bolabasket. Hasil pengembangan tes keterampilan fisik bermain bolabasket meliputi (1) tes kecepatan 3/4 basketball court sprint, (2) tes daya tahan aerobik bleep test, (3)) tes kelincahan lane agility test, (5) tes daya tahan otot core strange and stability test, (6) tes power tungkai vertical jump, (7) tes power lengan push-up, dan (8) tes fleksibilitas sit and reach. Dapat disimpulkan instrumen tes dapat digunakan sebagai metode evaluasi untuk mengukur kemampuan fisik bolabasket pada anak SMA.Kata Kunci: tes kemampuan fisik, bolabasket, siswa SMA putraÂ Developing a test of the physical capability for basketball for male students in the Province Of Yogyakarta Special TerritoryÂ AbstractThis study aims to develop a valid and reliable test of the physical capability for basketball to measure the level of the physical capability for basketball player among senior high school (SHS) students in Yogyakarta Special Territory (YST). The research subjects were 156 male SHS students in the Province of YST. The developed product was a test of the physical capability for basketball for male SHS students. The first to sixth steps belonged to the stage of developing standards for the indicators of the physical skills for playing basketball for SHS students. The seventh to tenth steps belonged to the stage of developing instrumens. The result of the small-scale testing was used as a product development tryout, conducted to test the validity and reliability of the test instrumens. A further test in the large-scale testing was focused on the construction of assessment norms and standards for the test instrumens for the physical skills for basketball. The results of the development of the test of the physical capability for playing basket include (1) a speed test of 3/4 basketball court sprint, (2) an aerobic endurance test of bleep test for basketball, (3) an agility test of lane agility test, (5) a muscle endurance test of core strange and stability test, (6) a heel power test of vertical jump, (7) an arm power test of push-up, and (8) a flexibility test of sit and reach all of these can used as an evaluation method to measure the physical capability for basketball among SHS students.Keywords: test of the physical capability, basketball, male SHS students